“Det er jo bare underholdning” – Om filosofi, populærkultur og underholdning - Nielsen, Carsten Fogh (Slagmark - Tidsskrift for idéhistorie, 2018)
The article argues for the legitimacy of regarding entertainment and popular culture as philosophically interesting and important topics. First it is shown that the conceptual distinction between “entertainment” and “art” is confused and that the normative implications often believed to follow from this distinction are problematic. Secondly it is argued that philosophy as a discipline is not confined to nor defined by an interest in particular topics (the Good, the Beautiful and the True for instance), but is better regarded as a reflective rational practice of questioning and examining whatever is of importance and interest to human beings. Bringing these two points together the article concludes by outlining some questions concerning entertainment and popular culture that philosophy might be uniquely suited to explore.